Identifying determinants for promoting public engagement via Chinese E-government TikTok in public health emergencies - Guo, Jingjing; Mohd Zawawi, Julia Wirza; Kamarudin, Syafila (Public Library of Science, 2025)
Background Social media have become vital tools for governments during public health crises, enabling the timely dissemination of critical information, health guidance, and public engagement. In China, public engagement through social media, particularly TikTok, presents unique challenges during crises. This study investigates the factors that predict public engagement via the Chinese government’s TikTok during a public health emergency, focusing on the roles of information quality, source credibility, multiple cues, immediate feedback, and trust as a mediating variable. Methods The study is grounded in the Elaboration Likelihood Model (ELM) and Media Richness Theory (MRT) to frame the relationships between these variables. Data were collected through an online questionnaire survey employing convenience sampling, involving 614 respondents aged 18–40 from Hebei Province, China. Descriptive statistical analysis was performed using SPSS, and Structural Equation Modeling (SEM) was employed to test the hypotheses. Results The findings indicate that information quality and immediate feedback are significantly positively associated with public engagement via the Chinese government’s TikTok. However, source credibility and multiple cues did not have a positive impact on public engagement. Additionally, the study reveals that trust mediates the relationships between information quality, source credibility, and immediate feedback with public engagement. Conclusion These results underscore the importance of trust in fostering public engagement and highlight the potential for enhancing government communication strategies on social media during crises. The study suggests that improving the quality of information and providing timely feedback can significantly increase public engagement through social media platforms like TikTok, particularly in the context of public health emergencies.